Rethinking "development": Land dispossession for the Rampal power plant in Bangladesh. (May 2020) - Mahmud, Muhammad Shifuddin; Roth, Dik; Warner, Jeroen
Highlights: The Rampal power plant project in Bangladesh radically changes land control. Land dispossessions are threatening agriculture-based rural livelihoods. This project-driven development mainly benefits rich and powerful social groups. Therefore Bangladesh's latest development narrative should be seriously questioned. Abstract: In this article, we critically review the developmental claims made for the construction of the Rampal power plant in southwestern Bangladesh, in the light of evidence about transformations of land control related to this construction project. Land has become a heavily contested resource in the salinity-intruded southwestern coastal area of Bangladesh. Changes in land control for the construction of the Rampal power plant and similar projects have intensified decades of struggles over rights and access to land. The Rampal project is labelled as "development" and claims to contribute to the elimination of poverty. However, we find that, in reality, this project leads to a reorganization of land control, rights and access in ways that perpetuate and intensify waves of eviction and exclusion of small landholders and landless laborers, thus threatening agriculture-based rural livelihoods. We analyze how four actor groups involved in land control are differently affected by the project interventions, embedded in the context of historical land tenure developments. We find that the benefits of this "development", primarily favoring rich and powerful social groups and investors, necessitates a critical rethinking of Bangladesh's development and its claims of poverty elimination in the light of related land control practices.